2011
DOI: 10.1111/j.1600-0838.2009.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exercise duration and intensity on the release of cardiac biomarkers

Abstract: Numerous studies have observed cardiac biomarker release with prolonged exercise. Despite this, we are unsure as to the constituent aspects of any given exercise bout that may be important in promoting cardiac biomarker release. This study examined the influence of exercise duration and intensity on the appearance of cardiac biomarkers. Twenty-one subjects ran for 45, 90 and 180 min at 85% and 95% of their individual anaerobic threshold on six different days randomized. Cardiac troponin I (cTnI) and N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
101
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(125 citation statements)
references
References 22 publications
(41 reference statements)
19
101
4
1
Order By: Relevance
“…The factors that influence the marked inter-and intra-subject variability in the exercise-associated cTn response are not fully understood but could not be explained in our data by exercise mode, duration, intensity, time of day, environment, or number of blood samples. Several previous studies observed a significant association between peak post-exercise cTnI and baseline level Serrano-Ostáriz et al, 2011). This was not the case for hs-cTnT in our study or in others (Legaz-Arrese et al, 2015;Saravia et al, 2010;Tian et al, 2014).…”
Section: Hs-ctnt Appearancecontrasting
confidence: 42%
“…The factors that influence the marked inter-and intra-subject variability in the exercise-associated cTn response are not fully understood but could not be explained in our data by exercise mode, duration, intensity, time of day, environment, or number of blood samples. Several previous studies observed a significant association between peak post-exercise cTnI and baseline level Serrano-Ostáriz et al, 2011). This was not the case for hs-cTnT in our study or in others (Legaz-Arrese et al, 2015;Saravia et al, 2010;Tian et al, 2014).…”
Section: Hs-ctnt Appearancecontrasting
confidence: 42%
“…This increase was found to correlate with exercise intensity (i.e. the more intense the exercise, the larger the increase) (11,25). A protocol involving gradual increases of 2 km.h -1 is not likely to provide enough data density to discriminate between the physiological profiles of elite athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the Tlim at the VMLSS or at a specific absolute velocity close to the VMLSS, the determination of the %VO 2max , %VMLSS, and/ or velocity developed for a two-hours duration would be probably more specific tests to evaluate marathon runners. It should be kept in mind that the performance of these types of tests is subject to a large degree of inter-subject variability (6,7,25) and is also sensitive to the effects of training (5). Interestingly, it has been shown that during a two-hour effort, swimmers select a strategy that allows them to develop the highest possible velocity and keep their serum lactate concentration stable (1).…”
Section: Discussionmentioning
confidence: 99%
“… Prolonged strenuous exercise leads to an elevation of cardiac specific biomarkers such as troponin T (TnT), troponin I (TnI), MB-creatine kinase (CKMB) and N-terminal pro brain natriuretic peptide (NT-pro BNP) in apparently healthy endurance athletes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These parameters are assumed to indicate cardiac injury or dysfunction [5,18] since troponin T and troponin I are highly specific markers of myocardial cell damage, even in the presence of simultaneous skeletal muscle damage [16].…”
Section: Introductionmentioning
confidence: 99%